Analisis Tata Kelola Arsitektur dan Perancangan Sistem Enterprise dalam Ekspedisi Barang pada Perusahaan Logistik - Yuniana Cahyaningrum (Jurnal Rekayasa Sistem Informasi dan Teknologi, 2023)
Architectural governance and company system design have an important role in ensuring the success of goods expeditions in logistics companies. Modern logistics companies increasingly face increasingly complex demands. In this case, there is a need for adequate integration of information technology and systems in optimizing operational activities. This research aims to analyze architectural governance and company system design in the context of goods expeditions in logistics companies. This research uses surveys and interviews with various stakeholders in logistics companies, such as executive level management, Information Technology (IT) departments, and field technical personnel. This research will discuss evaluating how a company's IT architecture and system design can influence the efficiency of operational activities, supply chain visibility, and the ability to respond quickly to market changes. It is hoped that the results of this research will provide insight into best practices in architectural governance and enterprise system design in the context of goods delivery. This can help logistics companies to improve their performance, reduce operational costs, and increase customer satisfaction. This research can provide future contributions regarding the understanding of the importance of having capital in information technology and effective architectural management in the ever-growing logistics goods expedition. With increasing competition and rapid change globally, understanding the right enterprise system design and IT architecture can be the key to the success of logistics companies in the future.